Amniote vertebral microanatomy – what are the major trends?. (August 2014) - Houssaye, Alexandra; Tafforeau, Paul; Herrel, Anthony
<x xml:space="preserve">Abstract</x> This contribution qualitatively and quantitatively analyses vertebral microanatomical features based on virtual sections of numerous amniote dorsal vertebrae obtained from conventional and synchrotron X‐ray microtomographic investigations. It demonstrates the great diversity of amniote vertebral microanatomy and highlights that it reflects structural, phylogenetic and ecological signals. Various microanatomical parameters appear to be strongly correlated with overall body size, which seems to be the principal structural constraint. A phylogenetic signal was detected but appears rather low. This study also reveals the peculiarity of squamates among amniotes, and notably of squamate fossorial taxa that show clearly distinct trends from those of the other fossorial amniotes, probably as they essentially use movements of the vertebral column rather than the legs to dig. Analyses based on habitat reveal several trends and two main tendencies concerning the tightness of the spongiosa (squamates excluded): a low number of relatively thick trabeculae in arboreal, flying and fossorial taxa, versus a high number of relatively thin trabeculae in aquatic forms. It also suggests that comparisons based on functional requirements, rather than habitat, would be more relevant. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 735–746.